The Effect of Using the Learning Cycle Strategy (5E’s) on Achievement and Development of Critical Thinking Skills in Science among Eighth Grade Students in Jordan - Al Totanji, Tweet Salim (Journal of Educational and Psychological Sciences, 2021)
The present study aimed to investigate the effect of using the learning cycle strategy (5E’s) on achievement and development of critical thinking skills in science among eighth grade students in Jordan. The study sample consisted of (53) female students who were intentionally selected from two divisions of the eighth grade class at the Al-Jubaiha Secondary School for Girls. 27) A female student, and an educational material was built in the living organisms unit and their environments from the science book for the eighth grade basic in the first semester, and an achievement test was built and a test for critical thinking was used. (5E’s) in raising the level of achievement and developing critical thinking skills in science among female students.